Decision Processes, Agency Problems, and Information: An Economic Analysis of Capital Budgeting Procedures - Marino, Anthony M.; Matsusaka, John G. (Review of Financial Studies, 2005)
Corporations use a variety of processes to allocate capital. This article studies the benefits and costs of several common budget procedures from the perspective of a model with agency and information problems. Processes that delegate aspects of the decision to the agent result in too many projects being approved, while processes in which the principal retains the right to reject projects cause the agent to strategically distort his information about project quality. We show how the choice of a decision process depends on these two costs, and specifically on severity of the agency problem, quality of information, and project risk.